(untitled) (قضايا سياسية, 2023)
It is too crucial to point that this research is trying to study the Homo Sacer in the state of Exception, Which the Italian Thinker Giorgio Agamben theorized in his political thought. Agamben thinks that this state is representative the core in the Western political thought, It has great rule in the theory of sovereignty and the establishment of state. Finding the Homo sacer who lives in a situation where his rights are violated. By disrupting the work of normal laws. It's what the state of exception does. The research was divided into three sections. The first discussed the state of exception and the paradox of sovereignty. The second section dealt with the Homo sacer and the bare life. The last topic was about Homo sacer and the crisis of contemporary Western democracy.Key words: the Homo sacer. The state of Exception. The Bare Life. The Sovereignty. The Democracy. Biopolitcs. Giorgio Agamben.